If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (12x + 66) + (2x + 20) = 9 Reorder the terms: (66 + 12x) + (2x + 20) = 9 Remove parenthesis around (66 + 12x) 66 + 12x + (2x + 20) = 9 Reorder the terms: 66 + 12x + (20 + 2x) = 9 Remove parenthesis around (20 + 2x) 66 + 12x + 20 + 2x = 9 Reorder the terms: 66 + 20 + 12x + 2x = 9 Combine like terms: 66 + 20 = 86 86 + 12x + 2x = 9 Combine like terms: 12x + 2x = 14x 86 + 14x = 9 Solving 86 + 14x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-86' to each side of the equation. 86 + -86 + 14x = 9 + -86 Combine like terms: 86 + -86 = 0 0 + 14x = 9 + -86 14x = 9 + -86 Combine like terms: 9 + -86 = -77 14x = -77 Divide each side by '14'. x = -5.5 Simplifying x = -5.5
| 2(3f+1)= | | -6(1+6x)-1= | | 4n+3(6n-1)=-135 | | 5(1/2-3) | | 2x-17=7x+12 | | 10x+9=7x+8 | | 8p+4=7+7p | | cx+b=5(x-c) | | 4-(3n-3)= | | -14y+28+6x=-44 | | -5*a+(-5*b)=3 | | 32+0.25y=50 | | log(x)=-22.7 | | 1/2•32= | | -268=12(x)-4 | | 8b+8(1-8b)= | | -268=4-12(x) | | 5/9x3/15 | | F(3)=1/2•32 | | 2x+-9(2)=9 | | 4-12(x)=-268 | | 2x+-9(0)=9 | | 9(12/7)+7= | | .55=log(x) | | 3x-6x+6=x-5+11 | | -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= | | -5y^2+8y-3=0 | | 16z+5z=-3 | | 10+11(x)=87 | | 3k^2-9k+5=0 |